Train-your-brain program to reduce depression, anxiety, and stress in stroke survivors: a pilot community-based cognitive intervention study - Tham, Xiang Cong; Phua, Vanessa Jing Xin; Ho, Evelyn Kit Yee; Yan, Tingting; Chen, Nicole Yun Ching; Zuo, Lijun; Thompson, Claire L.; Dong, Yanhong (Frontiers in Neurology, 2023)
Introduction Stroke is a major cause of death and disability worldwide, and it often results in depression, anxiety, stress, and cognitive impairment in survivors. There is a lack of community-based cognitive interventions for stroke survivors. This pilot single trial aimed to assess the feasibility, acceptability, and perceived effectiveness of a community-based cognitive intervention program called Train-Your-Brain (TYB) for stroke survivors and caregivers. The study focused on improvements in emotional and psychological well-being, as well as cognitive functioning. Methods A quasi-experimental design was used in this study. A total of 48 participants were recruited and assessed using Depression, Anxiety, Stress Scale – 21 items (DASS-21), Montreal Cognitive Assessment (MoCA) and Symbol Digits Modality Test (SDMT) before and after the intervention. The TYB program consisted of nine sessions and was conducted via the Zoom software application. Participants provided feedback on the program, highlighting areas for improvement. Results Twenty-seven stroke survivors and 21 caregivers completed the program. Participants expressed high satisfaction with the TYB program but recommended avoiding assessments in December and customizing the program for stroke survivors and caregivers. Stroke survivors showed significant improvements in depression and stress scores, while caregivers experienced no significant improvements after the program. While there was a slight improvement in stroke survivors’ cognitive scores after the program, it was not statistically significant. Caregivers, however, experienced a significant decline in cognitive scores. Discussion The TYB program provided group support and validation, resulting in improved mood and reduced stress among stroke survivors. Cultural collectivism played a significant role in fostering group cohesion. However, the program’s limited focus on caregivers and timing of assessments during the December holidays may have affected the outcomes. The TYB program demonstrated feasibility and potential effectiveness in alleviating psychological distress and enhancing cognitive function among stroke survivors. Future research should explore long-term effects, larger sample sizes, and non-English-speaking populations to enhance generalizability. Tailored interventions for caregivers are necessary.